Factors that contribute to the workplace injuries on the administrative staff at Bera District and Land Office, Pahang / Haslina Hamdan, Mahfuzah Mat Shah and Mardhati Mohd Yunos - Hamdan, Haslina; Mat Shah, Mahfuzah; Mohd Yunos, Mardhati (2010)
The researchers examined the factors that contribute to the employee's injuries in the workplace, at the same time to determine the effects and causes of the workplace injuries on Administrative Department at Bera District and Land Office. The factors that contribute to the workplace injuries can be classified as physical and psychological factors. The growing of the new technology like computer had increased somehow with the new injury like musculoskeletal problems such as carpal tunnel syndrome, repetitive strain injury, back pain, eye strain and many more. The researchers obtained data from questionnaires which consist of convenience sampling. The questionnaires were distributed to Administrative Department in Bera District and Land Office. The researchers found that office workers in this organization were suffering with carpal tunnel syndrome, back pain, eyes strain, headache and neck pain but the most common injury that these office workers were sufering was eye strain because they spent more time in front of the computer while the least injury was carpal tunnel syndrome.